The Impact of TVET Institute Directors’ Servant Leadership Style on Teachers’ Job Commitment in the Cambodian Context - Chamnan Sok; Sarom Mok; Kosal Thay; Morn Sokha; Saravuth Um (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
The quality, cost-effectiveness and leadership responsiveness necessary for Technical and Vocational Education and Training (TVET) are affected by the lack of active leadership, stakeholder participation and staff commitment. Also, TVET Institutes are not very valuable and are not regarded by some Cambodians as a form of higher education, such as college or university education. In light of that, the primary purpose of this study was to analyze the impact of TVET Institute directors' servant leadership (S-LEA) style in promoting TVET teachers’ job commitment (J-COM) in Cambodia. To achieve the study’s purpose, the three research questions were developed at the levels of S-LEA style practice, teachers’ J-COM, and the influence of S-LEA style practices on teachers’ J-COM. The quantitative research approach and correlational study design were employed. A total of 225 TVET teachers from 8 TVET Institutes in Phnom Penh City participated in this study, using a simple random sample that provided all teachers an equal chance of selection through the [1] sample size determination procedure. The research data were collected via a questionnaire and analyzed using quantitative methods, including one-sample t-tests, correlation analyses, and simple linear regression. The research found that S-LEA practice and teachers’ J-COM were at moderate levels. It was also revealed that a significant correlation existed between TVET Institute directors’ S-LEA style and TVET teachers’ J-COM (r(225) = 0.77, p < 0.01). As a result, the regression model shows that S-LEA practices are a significant predictor of teachers’ J-COM (f(1,222) = 157.792, p<0.01). This study makes significant contributions both theoretically and practically. TVET Institutes offer a number of advantages to all Cambodians. As a national technical training program, TVET Institutes have performed a number of vital functions, including boosting the economy, benefiting the private sector, supporting the educational system, and fostering the development of both professional and personal traits.